2022
DOI: 10.3390/polym14214767
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an Electrical Conductor, Strain Sensor, Electrical Connection and Cycle Switch Using Conductive Graphite Cotton Fabrics

Abstract: Researchers in science and industry are increasingly interested in conductive textiles. In this article, we have successfully prepared conductive textiles by applying a graphite dispersion to cotton fabric using a simple brush-coating-drying method and the solvents of dimethyl sulfoxide, dimethyl formamide, and a solvent mixture of both. The sheet resistance of the resulting cotton fabrics could be influenced by the type of polar solvent used to prepare the graphite dispersion and the concentration of graphite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Second, the peaks of the untreated cotton fabrics were also observed in this pattern. The XRD results shown in our study are consistent with the results of other studies published in the literature for cotton and graphite [43].…”
Section: Xrd Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…Second, the peaks of the untreated cotton fabrics were also observed in this pattern. The XRD results shown in our study are consistent with the results of other studies published in the literature for cotton and graphite [43].…”
Section: Xrd Analysissupporting
confidence: 92%
“…At the transition at 90 • C, the resistance increased, indicating a metallic behavior. In our previous study, it was reported that the resistance as a function of temperature showed semiconductor behavior only when the conductive cotton was prepared with graphite dispersed in DMF, DMSO, and a mixture of both [43]. This proves that graphite dispersed in ethanol affects the electrical behavior of the conductive cotton.…”
Section: Electrical Studiesmentioning
confidence: 86%
See 1 more Smart Citation
“…For fabrics with a conductive coating layer, Rsh becomes more relevant [57][58][59] because electrical conductivity relies heavily on the thin conductive coating formed primarily on the surface. Here, as a special case of ρs, it is better to use Rsh to evaluate the functions.…”
Section: Resistance and Resistivity In Conductive Textilesmentioning
confidence: 99%
“…The brush-coating-drying method was used by Alamer et al [21] to prepare conductive textiles from cotton using graphite and solvents DMSO and dimethylformamide (DMF). The lowest value of sheet resistance obtained by them was 0.47 kΩ/sq.…”
Section: Introductionmentioning
confidence: 99%